THE ROLE OF AVAILABLE RUBRIC TO ASSESS PRESENTING SKILLS IN PRE-SERVICE EFL TEACHING SYSTEM - Nurmurodova, Kamola (Журнал иностранных языков и лингвистики, 2021)
The article studies the target groups’ results whether they would give successful results on the task of performing presenting skills with specific rubric or without. The participants are the freshmen in foreign languages faculty at Pedagogical Institute. The research resulted better with the participants who prepared for the task with given rubric beforehand than the other ones and it gives the idea of that giving specific criteria to assess students for certain tasks particularly presenting ones provides more effects in language teaching and assessing.